Properties of Opiate-Receptor Binding in Rat Brain - Pert, Candace B. (1973)
[(3)H]Naloxone, a potent opiate antagonist, binds stereospecifically to opiate-receptor sites in rat-brain tissue. The binding is time, temperature, and pH dependent and saturable with respect to [(3)H]naloxone and tissue concentration. The [(3)H]naloxone-receptor complex formation is bimolecular with a dissociation constant of 20 nM. 15 Opiate agonists and antagonists compete for the same receptors, whose density is 30 pmol/g. Potencies of opiates and their antagonists in displacing [(3)H]naloxone binding parallel their pharmacological potencies.